Variational integrators for dynamical systems with rotational degrees of freedom - Leitz, Thomas; Leyendecker, Sigrid; Ober-Blöbaum, Sina (Proceedings of WCCM XI – ECCM V – ECFD VI, 2014)
For the elastodynamic simulation of a geometrically exact beam, a variational integrator is derived from a PDE viewpoint. Variational integrators are symplectic and conserve discrete momentum maps and since the presented integrator is derived in the Lie group setting (unit quaternions for the representation of rotational degrees of freedom), it intrinsically preserves the group structure without the need for constraints. The discrete Euler-Lagrange equations are derived in a general manner and then applied to the bea
UnivIS-Import:2015-04-16:Pub.2014.tech.FT.ltd.variat_90
Keywords: Discrete mechanics; Lie-group integrators; Variational integrators